Prawodawstwo wyznaniowe z okresu II Rzeczypospolitej we współczesnym polskim systemie prawnym - Borecki, Paweł (Wydawnictwo Naukowe UAM, 2014)
The following religious laws are still formally binding in the contemporary Polish legal system: ordinance of the President of the Republic of Poland of 22 March 1928 on the relationships between the State and the Eastern Old Rites Church without hierarchy chart, the Act of 17 March 1932 on the contributions payable to the Catholic Church, the Act of 21 April 1936 on the relationships between the State and the Muslim Religious Union in the Republic of Poland, the Act of 21 April 1936 on the relationship between the State and the Karaim Religious Union in the Republic of Poland, and the Act of 25 March 1938 on the production and trading in religious and cultic objects. Their compatibility with the current Constitution of 1997 raises certain doubts, while the regulations themselves contain some anachronisms and constitute an isolated phenomenon in the national legal system. What is more, these acts exist in separation from their primary historical context, including the axiological context and the context of the constitutional rights, which is particularly noticeable with regards the relationships between the State and religious unions. As it happens, the standards deriving from those laws have either entirely, or at least partially disappeared due to the desuetudo. From the perspective of a behaviourist approach, acts adopted in 1932 and 1938 are no longer binding whereas those of 1928 and 1936 have largely lost their applicability today. Further, the importance of pre-war religious legislation in the contemporary legal system in Poland is signifi cantly reduced. Most regulations, save for those of organisational nature or pertaining to the legal nature of religious unions and their organisational bodies, are impractical, inapplicable and out of use. What is more, these acts in their current form are not compatible with the principle of citizens’ confi dence in the state and obstruct development of confessional communities, and even undermine the State’s authority. As such they should be urgently repealed or modified.
Religious legislation of the Second Republic of Poland (1919–1939) in the contemporary Polish legal system
Keywords: State; Church relationships; pre-war religious legislation; Constitution of the Republic of Poland 1997; religious minorities